Premedication with sublingual or oral alprazolam in adults undergoing diagnostic upper gastrointestinal endoscopy - Shavakhi, Ahmad; Soleiman, Soghry; Gholamrezaei, Ali; Khodadoostan, Mahsa; Shavakhi, Sara; Tahery, Abdolmajid; Minakari, Mohammad (Endoscopy, 2014)
Background and study aim: Diagnostic esophagogastroduodenoscopy (EGD) is uncomfortable for most patients. We determined the efficacy of alprazolam, administered orally or sublingually, as premedication for sedation during EGD.Patients and methods: Adult EGD candidates were randomly allocated to four groups (n = 55, each group) and received alprazolam (0.5 mg) sublingually or orally, placebo sublingually or orally at 30 minutes before EGD. Main outcome measures included procedure-related anxiety and pain/discomfort (assessed using 11-point numeric scales), patient overall tolerance (assessed using a 4-point Likert scale), need for intravenous sedation, and willingness to repeat the EGD if necessary.Results: Patients experienced greater reduction in anxiety score after medication with sublingual alprazolam (mean 2.25, standard deviation [SD] 1.73) compared with sublingual placebo (mean 0.10, standard error [SE] 0.15]; P < 0.001) and oral alprazolam (0.63, SE 0.14; P < 0.001). Also, pain/discomfort scores were lower with sublingual alprazolam compared with sublingual placebo (3.29, SE 0.29 vs. 4.16, SD 1.86; P = 0.024), and with oral alprazolam compared with oral placebo (3.48, SD 1.69 vs. 5.13, SD 2.39; P < 0.001). Patient overall tolerance was better with sublingual alprazolam than with sublingual placebo (P = 0.005) or with oral alprazolam (P = 0.009). Regarding intravenous sedation, there was no difference between sublingual alprazolam and sublingual placebo (10.9 % vs. 10.9 %; P = 0.619) or between oral alprazolam and oral placebo (9.0 % vs. 12.7 %; P = 0.381). Willingness to repeat the procedure was greater with sublingual alprazolam than with sublingual placebo (50.9 % vs. 30.9 %; P = 0.026).Conclusions: Sublingual alprazolam is an effective premedication for sedation during EGD. It reduces anxiety and pain/discomfort related to EGD and increases patient tolerance and willingness to repeat the EGD if necessary.Clinical trial registration: NCT01949038 ClinicalTrials.gov